Molecular Docking, ADMET and Pharmacokinetic properties predictions of some di-aryl Pyridinamine derivatives as Estrogen Receptor (Er+) Kinase Inhibitors. Issue 1 (31st December 2022) - Abdullahi, Sagiru Hamza; Uzairu, Adamu; Shallangwa, Gideon Adamu; Uba, Sani; Umar, Abdullahi Bello
ABSTRACT: Breast cancer is one of the extensively diagnosed cancers and the dominating reason of women's cancer death globally. Selective estrogen receptor modulators (SERMs) such as Tamoxifen approved by the Food and Drug Administration (FDA) for the therapy of + breast tumors may cause negative side effects . Hence, there is urgent demand for more effective drugs to combat this disease. Molecular docking screening in combination with ADMET and drug likeness properties were utilized to examine the potency of 57 di-aryl and 2-anilino pyridinamine analogs as ER + protein receptor inhibitors. Nineteen compounds were found to have better docking scores than the control drug (Tamoxifen, MolDock score = −145.933, Rerank score = −112.169) among which compound 31 emerged as the most effective and potent candidate with best docking scores (MolDock score = −170.206 and Rerank score = −139.238). Furthermore, molecular dynamic simulation studies was performed using Desmond 2019–4 software package to justify the docking study using the docked complex of compound 31, the results confirm the rigidity of the protein-ligand structure during the simulation. The compounds possess drug-likeness and good ADMET properties as indicated by the results of pharmacokinetics studies performed as such they may be utilized as effective drug candidates for breast cancer treatment..